Empirical Equations for Analysis of Two-Way Reinforced Concrete Slabs - Fadhil, Hassan Ayad; Al-Ahmed, Ali Hussein Ali (Al-Khwarizmi Engineering Journal, 2012)
There are many different methods for analysis of two-way reinforced concrete slabs. The most efficient methods depend on using certain factors given in different codes of reinforced concrete design. The other ways of analysis of two-way slabs are the direct design method and the equivalent frame method. But these methods usually need a long time for analysis of the slabs. In this paper, a new simple method has been developed to analyze the two-way slabs by using simple empirical formulae, and the results of final analysis of some examples have been compared with other different methods given in different codes of practice. The comparison proof that this simple proposed method gives good results and it can be used in analysis of two-way slabs instead of other methods.